2022
DOI: 10.1002/cam4.4737
|View full text |Cite
|
Sign up to set email alerts
|

High recurrence of lymphedema and influencing factors in discharged breast cancer patients during the COVID‐19 pandemic: A multicenter, cross‐sectional survey

Abstract: Background There has been a delay in the detection and treatment of lymphedema in breast cancer patients during the lockdown owing to quarantine and limited social activity. Moreover, this scenario has caused psychosocial issues in these patients. Given that there is scarce information on the prevalence and influence of lymphedema during the coronavirus disease (COVID‐19) pandemic, we aimed to estimate the prevalence of lymphedema recurrence and its influencing factors among discharged breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In the clinical stages of BCRL, in addition to loss of the function of the affected limb, patients run the risk of skin sores and infections in the affected areas, which could exacerbate their condition further [31][32]. Chronic lymphedema is considered generally incurable[31], and recurring BCRL, which could further worsen its impacts, is not uncommon [33][34]. Above all, continuous treatment may be inevitable throughout the lifetime of survivors with chronic lymphedema; for example, patients with chronic venous insu ciency need regular external compression therapy for the rest of their lives[31].…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical stages of BCRL, in addition to loss of the function of the affected limb, patients run the risk of skin sores and infections in the affected areas, which could exacerbate their condition further [31][32]. Chronic lymphedema is considered generally incurable[31], and recurring BCRL, which could further worsen its impacts, is not uncommon [33][34]. Above all, continuous treatment may be inevitable throughout the lifetime of survivors with chronic lymphedema; for example, patients with chronic venous insu ciency need regular external compression therapy for the rest of their lives[31].…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study of breast cancer patients' experiences during the pandemic concluded that the challenges they faced, including lymphoedema, may have long‐term effects on their quality of life (Seven et al, 2021). In a multicentre survey of breast cancer patients in Wuhan (China), Peng et al (2022) found a high prevalence of persistent lymphoedema during the pandemic, with the associated risk factors being older age, radical surgery and radiotherapy. Patients with severe lymphoedema also experienced higher levels of psychological distress.…”
Section: Discussionmentioning
confidence: 99%